MANTLE CELL LYMPHOMA – A KILLER WITH A CHILD’S FACE - Krstić, Miljan; Stojnev, Slavica; Petković, Ivan (Acta medicae Medianae, 2022)
Mantle cell lymphoma (MCL) is a distinct type of non-Hodgkin lymphoma with very aggressive clinical behavior. Despite its bland morphology, MCL remains incurable and deadly disease, although several variants with more indolent clinical course have been recognized. This study aimed to comprehensively analyze pathological features of MCL in patients from Southearstern Serbia and to determine the frequency of this devastating disease in our population.  During the five-year period the diagnosis of MCL was established in 47 cases, which constitutes 10.3% of all newly diagnosed lymphomas in our Center for Pathology, University clinical center Nis. The majority of the patients were men, 72.3%, and the average patients’ age at the time of diagnosis was 66.1 years. Extranodal presentation was observed in 61.7%. Every fourth case of MCL was diagnosed on bone marrow biopsy. Oral cavity and gastrointestinal tract were equally represented as extranodal diagnostic location, with 17% respectively. MCL encompasses large spectrum of architectural patterns and cytological variants thus its diagnosis requires immunohistochemical analysis to CyclinD1 and SOX11 for correct diagnosis and distinction from other lymphoid neoplasms and reactive and hyperplastic conditions. Variant morphology of MCL may be easily confused with potentially curable or indolent lymphomas. Accurate and precise diagnosis of MCL may improve patients’ outcome through timely application of new and promising treatment strategies. Pathologist role in proper recognition and rapid diagnosis of MCL and its subtype, especially in biopsies from extranodal locations, including endoscopic biopsies, may contribute significantly to longer survival and better clinical outcome of the disease.
Keywords: Mantle cell lymphoma, diagnosis, pathology, immunohistochemistry, CyclinD1